2019
DOI: 10.3389/fcimb.2019.00403
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Alterations Induced by Long-Term Axenic Cultivation of Leishmania amazonensis Promastigotes With a Multiplatform Metabolomic Fingerprint Approach

Abstract: Leishmaniases are widespread neglected diseases with an incidence of 1.6 million new cases and 40 thousand deaths per year. Leishmania parasites may show distinct, species-specific patterns of virulence that lead to different clinical manifestations. It is well known that successive in vitro passages (SIVP) lead to the attenuation of virulence, but neither the metabolism nor the pathways involved in these processes are well understood. Herein, promastigotes of a virulent L. amazonensis strain recently isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 100 publications
(162 reference statements)
0
2
0
1
Order By: Relevance
“…Several studies have shown that the long-term culture of L. infantum, L. major, and L. amazonensis alters the expression of virulence factors, changes the parasite metabolism, and impairs their ability to infect mice [28,[31][32][33][34]. Although these studies are still in their infancy, they shed light on the importance of evaluating the loss of infectivity of Leishmania after a long period of culture when in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that the long-term culture of L. infantum, L. major, and L. amazonensis alters the expression of virulence factors, changes the parasite metabolism, and impairs their ability to infect mice [28,[31][32][33][34]. Although these studies are still in their infancy, they shed light on the importance of evaluating the loss of infectivity of Leishmania after a long period of culture when in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is highly speculative; however, studies on parasites that lost one of these two virulence factors showed a decrease in their ability to infect macrophages and mice [37][38][39]. In addition, [34] showed that the L. amazonensis cultured for a long-term duration was less infective in vitro compared to the parasites recently recovered from an in vivo infection. Therefore, it is important to highlight the importance of carrying out studies with virulent parasites since their passage for long periods in culture can alter the phenotypic and infective characteristics of the parasites.…”
Section: Discussionmentioning
confidence: 99%
“…A metabolômica foi utilizada para caracterizar o metabolismo do parasita (Akpunarlieva et al, 2017;Castilho-Martins et al, 2015;Crepaldi et al, 2019;Saunders et al, 2014;Westrop et al, 2015) e se mostrou uma ferramenta útil, uma vez que os mecanismos de controle pós-transcricionais e pós-traducionais dificultam o acesso ao fenótipo do parasita utilizando apenas transcriptômica e proteômica (Scheltema et al 2010;Kloehn et al 2015;Atan et al 2018).…”
Section: Metabolômica No Estudo De Leishmaniosesunclassified